2021
DOI: 10.1111/ans.17078
|View full text |Cite
|
Sign up to set email alerts
|

Influence of patellar denervation on anterior knee pain and knee function following total knee replacement: a systematic review and meta‐analysis

Abstract: Background: Previous studies have reached mixed results regarding the effects of patellar denervation with electrocautery (PD) on total knee replacement (TKR). This systematic review and meta-analysis aimed to summarize all available literatures to investigate the influence of PD on postoperative anterior knee pain (AKP) and knee function after TKR. Methods: Electronic databases, including PubMed, Cochrane Library and Embase, were searched from their inception to March 2021. Randomized controlled trials (RCT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The median values of OKS, WOMAC as well as KOOS Symptoms and Pain components of the present study were all within the 4th quartile (within the upper 75–100%) of mean values reported in recent systematic reviews and/or meta‐analyses on TKA [10, 12, 14, 15, 23, 24, 26, 27, 29, 30, 38, 41–44]. The median values of FJS as well as the ADL, Function and QOL components for KOOS were all within the 3rd quartile (within the upper 50–75%) of mean values reported in recent systematic reviews and/or meta‐analyses on TKA (Fig.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The median values of OKS, WOMAC as well as KOOS Symptoms and Pain components of the present study were all within the 4th quartile (within the upper 75–100%) of mean values reported in recent systematic reviews and/or meta‐analyses on TKA [10, 12, 14, 15, 23, 24, 26, 27, 29, 30, 38, 41–44]. The median values of FJS as well as the ADL, Function and QOL components for KOOS were all within the 3rd quartile (within the upper 50–75%) of mean values reported in recent systematic reviews and/or meta‐analyses on TKA (Fig.…”
Section: Resultssupporting
confidence: 76%
“…Comparison of patient‐reported outcome measures (PROMs) to pooled results in systematic reviews and/or meta‐analyses on OTS TKA. Footnotes: 1 Rudran et al [41] (5 studies); Elbardesy et al [14] (4 studies); Li et al [27] (2 studies); Qin et al [38] (3 studies); Tso et al [43]; Deng et al [12] (3 studies); Gao et al [15] (4 studies); Kim et al [24] (2 studies); Luo et al [29] (4 studies). 2 Tso et al [43] (5 studies); Cacciola et al [10] (2 studies); Luo et al [29] (2 studies).…”
Section: Resultsmentioning
confidence: 99%
“…Patellar denervation is an electrocautery technique demonstrated to significantly reduce rates of anterior knee pain in tKa for both resurfaced and unresurfaced knees by recent meta-analyses. [64][65][66][67] Patellar denervation was used in five studies included in this meta-analysis, either in both groups or just the unresurfaced knees. 30,31,37,40,44 Patelloplasty is a vaguely defined intervention that aims at reshaping the patella for optimal articular tracking in the trochlea and is often used instead of patellar resurfacing in unresurfaced patellae.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PD with electrocautery has the theoretical advantage of reducing the occurrence of postoperative AKP by regulating these pain receptors. Several studies have demonstrated that PD effectively improves AKP after TKA without resurfacing the patella [27, 35, 40, 42]. However, the evidence on PD for pain reduction is conflicting.…”
Section: Discussionmentioning
confidence: 99%